Wakaf Kolektif dalam Persfektif Hukum Islam & Hukum Indonesia: Studi Kasus Rumah Sakit Achmad Wardi, Banten: Collective Waqf in the Perspective of Islamic Law & Indonesian Law: Achmad Wardi Hospital Case Study, Banten - Yuli Yasin (Direktorat Jenderal Bimbingan Masyarakat Islam, 2023)
Along with the increasing number of social institutions applying for permits as nazhir for cash waqf to the Indonesian Waqf Board (BWI), more and more waqf platforms offer variety of programs. Through these platforms, waqif may choose to contribute to the programs of interest according to their financial abilities. Lack of funds for that particular program will be fulfilled by other waqif who have an interest in the same program. The program will continue to be offered until the target funds needed are accomplished, and accordingly one program of waqf consists of several wakifs. This kind of waqf practice is known as collective waqf. This study seeks to explore the status of collective waqf in Islamic law and Indonesian positive law. It also addresses its urgency in the new trend of waqf practices in Indonesia through examining the case of collective waqf mobilized by the Indonesian Waqf Board (BWI) in building Achmad Wardi Eye Hospital (RSAW) in Serang, Banten. Using a qualitative method of descriptive analysis, this research confirms the legality of collective waqf according to both Islamic law and positive law. Even though the Waqf Law No. 41 of 2004 does not specifically state its permissibility, the guidelines mentioned in Indonesian Waqf Board (BWI) Regulation No. 1 of 2009 concerning the management and development of movable waqf assets in the form of money has provided certain procedures for collective cash waqf. This legal provision implicitly confirms the permissibility of collective waqf. This research also proves that collective waqf increase community's participation to development program for public facilities by fulfilling waqf according to their individual capabilities. The success story of collective waqf organized by the BWI in building and developing Achmad Wardi Eye Hospital becomes a model how collective waqf institution plays important role in providing public health facility built on waqf land with non-governmental funds through cash waqf organization.